Relationship of sex-role orientation to two measures of self-esteem - İnelmen, Kıvanç V. Ö., 1969- (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 1996., 1996)
The inquiry in the present study was concerned with how people's attitude towards their own identity, or perceived worthiness, i.e., self-esteem, and their sex-role identity relate to each other, and how these two cognitions are influenced by the possible forms of relationship depending on the culture. For that purpose, data were collected from a group of university students (N=139), using a sex-role inventory and two self-esteem inventories which were designed to measure separate aspects of selfesteem. As hypothesized, the global self-esteem of the men and women respondents did not significantly differ, although their satisfaction with, and the importance they attributed to specific sources of self-esteem diverged markedly. The results suggested that these source specific differences in self-esteem were in accordance with social role expectations from men and women. More specifically, whereas in men individuating characteristics were more salient, among women the interpersonal bonds were more consequential. The present results also provided support for the hypothesis that sex-role orientation, rather than biological sex, is related to selfesteem. The evidence provided partial support for both the androgyny and masculinity models. The findings were in line with the proposition that traditional sex-role socialization is undergoing change in higher socioeconomic sectors of the society, and this change is more evident in young, educated, urban groups. The results were Cliscussed in terms of the individualism-collectivism dichotomy.
Keywords: Self-esteem.; Sex role.